INFEKSI MENULAR SEKSUAL DAN RIWAYAT KONTRASEPSI HORMONAL SEBAGAI FAKTOR RESIKO LESI PRA-KANKER LEHER RAHIM - weni tri purnani; siswi wulandari; Anita Nuril Fadila; Nuridani nuridani (Jurnal Bidan Pintar, 2021)
Background and purpose: Currently examination with IVA and pap smear for pre-cervical lesion screening has been carried out in East Java Province. This study aims to find out hormonal contraceptives and the history of STIs as risk factors for pre-cervical cancer lesions. Method: The research design is a case-control with a sample of 76 PUS women who were positively diagnosed with pre-cancerous lesions with IVA examinations and confirmation of pap smear examinations at two health centers in Kediri City from February to July 2020. Control as many as 76 PUS women were selected from those who were negative in the same period. Case samples and controls are selected consecutively. Data on risk factors is collected through interviews using questionnaires. Data analysis is done by logistic regression method to get adjusted odd ratio of each risk factor. Result: Multivariate analysis showed that hormonal contraceptive use (>5 years and <5 years) increased the risk of pre-cervical lesions compared to those who did not use hormonal contraceptives respectively with OR=10.7 (95%CI:1.04-108.17) and OR=3.0 (95% CI: 1.16-7.84). A history of STIs also increases the risk of pre-cancerous cervical lesions by OR=9.7 (95%CI: 3.83-24.18).Conclusion: The use of hormonal contraceptives and a history of sexually transmitted infections increases the risk of pre-cervical lesions.